The role of changes in the Tariff agreement in the field of compulsory health insurance for assessing the effectiveness of medical organizations - E. V. Smirnova (Здоровье мегаполиса)
The development of an evaluative approach to determining the effectiveness of medical organizations, the introduction of various indicators for assessing the provision of medical care is one of the mechanisms for improving its quality and accessibility for the population. Correction of regulatory legal documents regulating the activities of the sphere of compulsory medical insurance, taking into account changes, including those taking place in the healthcare of the Russian Federation as a whole, is a necessary requirement for updating approaches to the selection of adequate assessment criteria.